Radiation-Induced Breast Angiosarcoma after Conservative Surgery for Breast Cancer - Miyata, Mami; Yoshida, Nao; Ishizuka, Mariko; Umezaki, Nodoka; Yoshikawa, Katsuhiro; Sueoka, Noriko; Tsubota, Yu; Yamamoto, Daigo; Sekimoto, Mitsugu (Gan to kagaku ryoho, 2020)
We present the case of an 88-year-old woman who had undergone breast conserving surgery for left breast cancer 8 years ago.She received postoperative radiotherapy(total dose of 60 G/30 Fr)to the residual breast together with endocrine therapy.She underwent skin biopsy after having had a red skin tumor in the left breast.Angiosarcoma was diagnosed and chemotherapy and radiotherapy were initiated.The patient is alive without recurrence 8 months after chemotherapy.